2005
DOI: 10.2174/156801605774322274
|View full text |Cite
|
Sign up to set email alerts
|

Modulators of Ion Channels Activated by Hypotonic Swelling in Cardiomyocytes: New Perspectives for Pharmacological Treatment of Life-Threatening Arrhythmias

Abstract: This review highlights the most important research data related to membrane potential and current changes in cardiomyocytes during hypotonic stress. Relative decrease in osmolarity in extracellular compartment (due to accumulation of metabolic products in the cells) during acute episodes of ischemia in the heart muscle leads to cell swelling caused by water entering the cells. Such condition starts regulatory volume decrease (RDV) in cardiomyocytes--a process involving activation of various ion channels. It se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Following the electrophysiological remodeling of the atria, changes in the structure of the atria start to follow. One of the structural changes is the dilatation of atrial myocyte plasma membrane (11,12), increasing the I Ks currents in the cells and aggravates the atrial remodeling (16,19). The present study found that losartan attenuated both the I Ks increase and the APD (26,27), providing clinical support for our experimental speculation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Following the electrophysiological remodeling of the atria, changes in the structure of the atria start to follow. One of the structural changes is the dilatation of atrial myocyte plasma membrane (11,12), increasing the I Ks currents in the cells and aggravates the atrial remodeling (16,19). The present study found that losartan attenuated both the I Ks increase and the APD (26,27), providing clinical support for our experimental speculation.…”
Section: Discussionsupporting
confidence: 81%
“…Hypo-S-induced stretch of atrial myocytes fits the stretch of myocardial cell membrane, generally causing the various transport changes of related ion channels (including the increase of I Ks in atrial myocytes) in the early stage of AF (11,16,(18)(19)(20). Figure 2a-2e shows the typical I Ks current curves elicited by depolarizing voltage-clamp steps given from a −50 mV holding potential to various test potentials in the presence of Iso-S (panel A), Hypo-S (panel B), Hypo-S+1 μM losartan (panel C), Hypo-S+10 μM losartan (panel D), and Hypo-S+20 μM losartan (panel E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyers et al, 2006). Deregulation of cell volume homeostasis, on the other hand, has been related to different pathophysiological conditions including, but not only, cerebral edema, hypercatabolic states, diabetes mellitus, chronic renal failure, sickle cell disease and uraemia (Strange, 1992;McManus et al, 1995;Waldegger et al, 1998;Won et al, 2002;PasantesMorales et al, 2002b;Haussinger, 2004;Bringmann et al, 2005;Kimelberg, 2005;Kocic, 2005;Leis et al, 2005;Norenberg et al, 2005Norenberg et al, , 2007Sterns and Silver, 2006;Verbalis, 2006;Liang et al, 2007;Mongin, 2007;Rosenblum, 2007).…”
mentioning
confidence: 99%
“…Also, as ICl swell is involved in numerous pathophysiological processes 67 , its pharmacological inhibition is regarded as a potential strategy in the treatment of several life-threatening conditions. For example, in the heart, blockers of Cl − currents such as ICl swell may have antiarrhythmic properties 68,69 . Furthermore, pharmacological inhibition of ICl swell antagonizes apoptosis by preventing apoptotic volume decrease and downstream apoptotic events 70 .…”
Section: Discussionmentioning
confidence: 99%